Myrthue, et gårdsanlæg fra jernalder - Thomsen, Niels (Kuml, 1964)
Myrthue-an Iron-Age farm complex On a little sandy promotory, running out from the northeast comer of Marbæk plantation into the water-meadows of the Varde river, on the farmstead of Myrthue northwest of Esbjerg, excavations conducted since 1959 by Esbjerg Museum have uncovered the remains of four burnt buildings of Early Roman lron-Age date. A burial, clearly of the same date as the settlement, and lying eighty yards away in the direction of the coast, is described elsewhere in this issue. Houses of this period have been found in large numbers in the Esbjerg area during the last 15 years, but the Myrthue site revealed, not the well-known long-houses with dwelling house and cattle shed beneath the same roof, but 3 quite short buildings which can only have been used as dwellings or workrooms, as well as a cattle-shed with a cobbled floor and a sunk gutter of the type now well-known in the district. Despite careful investigation no trace could be found of the dwelling quarters to the west which are normally associated with such cattle quarters, and it thus appears that we have here, for the first time on an lron-Age site, a separate cattle shed (Fig. 2). Between the houses lay a cobbled road-system, including a crossroad with very neatly constructed edge-stones and gutters (Figs. 1 & 3). One of the streets ran up to the massive southern threshold stone of House 1, continued within the house as a paving of smaller stones, and ran on through the doorway in the northern wall (Fig. 4). The outlines of the houses were clearly marked by the thick, reddish-brown layer of ash and by the remains of the clap-daubed wattle walling. All four buildings possessed very clearly rounded corners, a feature noted in other settlements of this period. House 1 and House 2 were oriented E-W, though a degree or so towards SE-NW as can normally be seen to have been the case in other published plans of Jutland Iron-Age houses. House 1 measured 9 X 4.5 meters, divided into two portions by the flagging noted above. Remains of 3-4 pottery vessels were found on this surface, and fragments of larger vessels in the western portion of the house. Here too was found the buried vessels which appears in every self-respecting Iron-Age house, presumably an offering to underground powers (Fig. 11). The hearth lay in the eastern half, and consisted of a layer of clay ornamented with a linear pattern (Fig. 5). Here too there was a pit, about 75 cms. deep and measuring about 120 X 80 cms. It was open when the house was burnt, and may have been a work-pit, allowing a craftsman to work with the floor as his work-table. This feature, together with the absence of cattle-quarters, may suggest that the building was the home of some craftsman. House 2 was smaller, 6.6 meters in length and with a width varying from 3.5 to 4 meters. It contained a central hearth and a large quantity of pottery fragments. Here, too, a pottery vessel had been buried, under a flat stone, while immediately to the west of the cobbled entrance lay the butt end of a stone battleaxe of the Jutland Single-Grave culture. Such axes, as well as flint axes and fossils, have been found in other Iron-Age settlements and graves, and the merits of Stone-Age relics as charms against fire and lightning have been recognised up until recent times-though notably ineffective in this case. House 3, running N-S and measuring 5 X 3.5 meters, showed clear ash levels and remains of clay plastering, but was completely devoid of contents (Fig. 9). House 4 was the cattle shed, with cobbled floor and sunk gutter (Fig. 10). It measured about 11 meters in length, with a width of 4.5-5 meters. The gutter ran, as is usual in the cobbled cattle-quarters of the area, towards the east end of the building, but it did not follow the normal practice of running out in the open air, running instead into a stone-lined pit, about 75 cms. deep, a yard and a half short of the end wall. This pit must have been for the collection of liquid manure, and it is possible that a 54 cm. high pottery vessel, sunk into the ground near the southeast corner of the building, was for the same purpose, the liquid being collected for dyeing or for tanning. In the northeast corner there was another buried vessel, with a smaller vessel inverted above it as a lid (Fig. 11). Traces of two more houses, much disturbed by the plough, were found in the area excavated, and more undoubtedly lie close by in the field. At three other places in the immediate vicinity potsherds of Roman Iron-Age date and stretches of cobbles have been found, and it would probably be more correct to talk of a more or less connected series of farms along the steep coastal slope than to name each of the sites a separate village. An extensive system of field-dykes covering the greater part of the 500-acre Marbæk plantation and traceable in the fields beyond should probably be considered as associated with this string of Iron-Age settlements. Niels Thomsen